2016
DOI: 10.1007/s10661-016-5663-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties and species composition under different grazing intensity in an alpine meadow on the eastern Tibetan Plateau, China

Abstract: As the main form of land use and human disturbance of grassland, livestock grazing has great influences on the soil resources and plant communities. This study observed the variation of soil properties and community characteristics of four treatments of different grazing intensity (no grazing, UG; light grazing, LG; moderate grazing, MG; and heavy grazing, HG) in an alpine meadow of Sichuan Province on the northeastern margin of the Tibetan Plateau. The results showed that grazing increased the pH, soil bulk d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Those soil chemical properties had an abundance of direct linkage between them. The pH and Na showed higher values at 0-10 cm of SD across all grazing level, especially at the OG site of HE, and this was due to the high distribution of sand soil particles and a positive relationship with pH and Na (Tufa et al, 2019;Yang et al, 2016;Wolka et al, 2011). As pH increases, the availability of certain major basic cations like Na, clay, and CEC are positively correlated because clay minerals provide the negative charge to attract the cations.…”
Section: Grazing Intensity Impact On Soil Chemical Propertiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Those soil chemical properties had an abundance of direct linkage between them. The pH and Na showed higher values at 0-10 cm of SD across all grazing level, especially at the OG site of HE, and this was due to the high distribution of sand soil particles and a positive relationship with pH and Na (Tufa et al, 2019;Yang et al, 2016;Wolka et al, 2011). As pH increases, the availability of certain major basic cations like Na, clay, and CEC are positively correlated because clay minerals provide the negative charge to attract the cations.…”
Section: Grazing Intensity Impact On Soil Chemical Propertiesmentioning
confidence: 94%
“…Rangelands are lands on which the indigenous vegetation is predominantly grasses, grass-like plants, forbs, or shrubs and is managed as a natural ecosystem (Raj, 2005). Arid and semi-arid rangelands are heterogeneous in space and time because of variation in biotic and abiotic factors related to vegetation and soil properties and provide multiple ecosystem functions and services (Wang et al, 2016;Yang et al, 2016). Rangeland heterogeneity shapes vegetation structure and productivity (IPCC, 2013;Yigini and Panagos, 2016;Ademe et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, Yang et al (2016) reported no significant relationship between the richness and grazing intensity in the Tibetan Plateau. The results indicated that the magnitude of the grazing intensity may not be a key factor influencing richness (Deng et al 2014b).…”
Section: Resultsmentioning
confidence: 94%
“…Livestock grazing is the main form of land use and human disturbance on grassland vegetation (Díaz et al, ; Yang et al, ; Yun & Wesche, ). Recent researches (Caccianiga et al, ; Pierce et al, ) showed that, as an important driver of vegetation structure and community composition at α scale, disturbance (e.g., grazing, mowing, fire, and Till) would result in loss of biomass and reallocation of resource (e.g., light and space) and thus altered the pattern that S‐selected strategy dominated.…”
Section: Discussionmentioning
confidence: 99%